Future Direction of Job Creation Programs in Korea - Yong-seong Kim (Korea Development Institute (KDI), 2015)
- This paper aims to overview the current state of the government-funded job creation programs and then to discuss the programs' future direction for an effective improvement in the employment rate based on international comparison and empirical analysis. - The government's budget for the job creation programs has steadily increased in recent years to reach KRW 11.8 trillion (based on the budget plan) in 2014. - By sub-program related to the active labor market policy, Korea's budget spending was overwhelmingly concentrated on direct job creation (67.3 percent in 2010) while the spending was relatively minuscule on vocational/education training (17.2 percent) and employment services (2.7 percent). - In contrast, OECD countries spent a greater amount on vocational/education training and employment services (28.5 percent on average in 2010) than on direct job creation (12.5 percent on average). - An empirical analysis on the short- and medium-term effects of active labor market policy using OECD country data shows the following: - Employment subsidies and direct job creation worked to raise the employment rate in the short-term while the medium-term effects were not confirmed. Of note, direct job creation was found to have negative effects in the medium-term. - Employment services and vocational/education training helped boost the employment rate in the medium- to long-term. - A review on the reallocation of current budget for the job creation programs is necessary. - The government needs to gradually cut the spending share on direct job creation, whose medium- to long-term effects are in question. - Instead, it would be ideal for the government to shift the focus of its financial resource allocation over to employment services and vocational/education training, on which it currently spends relatively little. - To boost female employment rate, expansion of part-time work and more effective child care policy is needed. - OECD country data shows that the larger the proportion of part-time employees there are in a market, the higher the female employment rate tends to be. In addition, child care policy is considered a key determinant of a country's female employment rate. - Therefore, the government needs to improve its policy efforts to increase penetration of flexible part-time employment and to support the work-family life balance.
Keywords: 330